Revealing the Impact of Critical Stellar Central Density on Galaxy Quenching through Cosmic Time - Bingxiao Xu; Yingjie Peng (The Astrophysical Journal, 2024)
In a previous work, we investigated the structural and environmental dependence on quenching in the nearby universe. In this work, we extend our investigations to higher redshifts by combining galaxies from the Sloan Digital Sky Survey and The FourStar Galaxy Evolution surveys. In low density, we find a characteristic Σ _1 kpc above which the quenching is initiated as indicated by their population-averaged color. ${{\rm{Σ }}}_{1\,kpc}^{crit}$ shows only a weak mass dependency at all redshifts, which suggests that the internal quenching process is more related to the physics that acts in the central region of galaxies. In high density, ${{\rm{Σ }}}_{1\,kpc}^{crit}$ for galaxies at z > 1 is almost indistinguishable from their low-density counterparts. At z < 1, ${{\rm{Σ }}}_{1\,kpc}^{crit}$ for low-mass galaxies becomes progressively strongly mass dependent, which is due to the increasingly stronger environmental effects at lower redshifts. ${{\rm{Σ }}}_{1\,kpc}^{crit}$ in low density shows strong redshift evolution with ∼1 dex decrement from z = 2.5–0. It is likely that at a given stellar mass, the host halo is on average more massive and gas-rich at higher redshifts; hence, a higher level of integrated energy from a more massive black hole (BH) is required to quench. As the halo evolves from the cold to hot accretion phase at lower redshifts, the gas is shock-heated and becomes more vulnerable to the feedback processes from active galactic nucleus as predicted by theory. Meanwhile, angular momentum quenching also becomes more effective at low redshifts, which complements a lower level of integrated energy from the BH to quench.